How Does Illiquidity Affect Delegated Portfolio Choice? - Dai, Min; Goncalves-Pinto, Luis; Xu, Jing (Journal of Financial and Quantitative Analysis, 2019)
In response to how they are compensated, mutual fund managers who are underperforming by mid-year are likely to increase the risk of their portfolios toward the year-end. We argue that an increase in the liquidity of the stocks that managers use to shift risk can lead to an increase in the size of their risky bets. This in turn hurts fund investors by increasing the costs of misaligned incentives associated with delegated portfolio management. We provide both theoretical and empirical results that are consistent with this argument. We use decimalization as an exogenous shock to liquidity to identify causal effects.